Evaluating the Partial Fibulectomy on Stress Distribution in Tibiofemoral Joint: Evaluating the Partial Fibulectomy on Stress Distribution in Tibiofemoral Joint - Tabatabaei, Mohammad (Regeneration, Reconstruction & Restoration (Triple R), 2020)
Introduction: Partial fibulectomy has been suggested for patients who encounter with severe varus/valgus or ununited fractures of the tibia. This study develops a finite element (FE) model of partial fibulectomy to study stress distribution in the tibiofemoral joint. Materials and Methods: A 3D magnetic resonance imaging (MRI)-based of tibiofemoral joint and FE model was developed for study from a man volunteer with the normal left knee. Components consisted of the exact geometry of femur, tibia, fibula, meniscus, and articular cartilages. Firstly, geometries were constructed in Mimics and then exported to Rapid Forming XOR2 and finally, the Computer-aided design (CAD) model was analyzed in ABAQUS 6.10. Mechanical properties of the model for soft tissues were considered to be linear elastic, isotropic and homogenous and for bony parts were considered to be rigid. Results: Model predictions were compared with normal one and used to derive stress distribution under physiological loading for standing in quasi- static condition. The results showed load transferring toward lateral condyle due to partial fibulectomy. The variation of stress distribution would increase the risk of osteoarthritis. Conclusion: Our results have been predicted that partial fibulectomy could be an unknown risk factor for osteoarthritis and the model could be used for extended similar studies.